Classification of Reviews on Mobile Phones Using Text Mining Techniques - Davis, Livin; Vaidhehi, V (International Journal of Engineering and Technology, 2018)
People register their opinion or feedback regarding the products in different forum. This research work is based on the classification of reviews regarding the different mobile phones. Dataset from Amazon pertaining to the opinions for mobile phones is used in this work. Opinion which is expressed as text is classified as positive opinion or a negative opinion using text mining techniques. Opinion mining helps to understand the customers in a better way. This work shows the visual representation of words by using word cloud and to classify the reviews on a two point scale. From the dataset, randomly 197 reviews are taken out of which 148 reviews are classified as positive, 49 reviews are classified as negative. Â